Guiding Excellence: Enhancing Learning Quality through Consultative Supervision in Madrasah - Muhammad Zuhdi Hasan (Journal of Educational Management Research, 2023)
The quality of learning in madrasah is a crucial factor in achieving the goal of quality education. This study aims to understand the improvement of learning quality based on consultative supervision in madrasah. The research method used is qualitative with a case study approach. This approach is used to understand the aspects of improving the quality of learning based on consultative supervision in madrasah. The research informants were supervisors, heads and teachers in several madrasahs in Probolinggo district. Data were collected through interviews, observation and analysis of relevant documents. The results show that the consultative supervision process is carried out through the activities of providing time for consultation, problem solving in learning and collaboration between supervisors and madrasah heads in improving learning quality.